Analysis of the influence of river discharge and wind on the Ebro turbid plume using MODIS-Aqua and MODIS-Terra data - Fernández-Nóvoa, D.
The turbid plume formed at many river mouths influences the adjacent coastal area because it transports sediments, nutrients, and pollutants. The effects of the main forcings affecting the Ebro turbid plume were analyzed using data obtained from the Moderate Resolution Imaging Spectroradiometer (MODIS) sensor onboard the Aqua and Terra satellites over the period 2003–2011. Composite images were obtained for days under certain river discharge conditions (different flow regimes) and different types of wind (alongshore and cross-shore winds) in order to obtain a representative plume pattern for each situation. River discharge was the main driver of the Ebro River plume, followed by wind as the secondary force and regional oceanic circulation as the third one. Turbid plume extension increased monotonically with increased river discharge. Under high river discharge conditions (N355 m3 s−1), wind distributed the plume in the dominant wind direction. Seaward winds (mistral) produced the largest extension of the plume (1893 km2), whereas southern alongshorewinds produced the smallest one (1325 km2). Northern alongshore winds induced the highest mean turbid value of the plume, and southern alongshore winds induced the lowest one. Regardless of thewind condition,more than 70% of the plume extensionwas located south of the river mouth influenced by the regional oceanic circulation.